2016
DOI: 10.1080/01616412.2016.1258970
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulsatility and resistance indices of cerebral arteriovenous malformation feeder arteries after embolization and surgery

Abstract: Following partial AVM embolization, PI, RI are unchanged and flow velocities in feeder arteries also remain unchanged likely due to redistribution of flow through residual nidus. Thus, staged management of AVMs is unlikely to increase outflow resistance and offers a safe treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Using quantitative MRA to measure blood flow in cerebral AVMs before and after embolization and surgery, Shakur et al demonstrated that blood flow in the ipsilateral artery decreased and normalized in comparison to the contralateral artery after both embolization and surgery. 30 This study replicates these findings in this cohort of patients treated with SRS. In contrast, Shakur et al demonstrated that pulsatility in the ipsilateral artery increased after only surgery and not embolization.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Using quantitative MRA to measure blood flow in cerebral AVMs before and after embolization and surgery, Shakur et al demonstrated that blood flow in the ipsilateral artery decreased and normalized in comparison to the contralateral artery after both embolization and surgery. 30 This study replicates these findings in this cohort of patients treated with SRS. In contrast, Shakur et al demonstrated that pulsatility in the ipsilateral artery increased after only surgery and not embolization.…”
Section: Discussionsupporting
confidence: 81%
“…This study replicates these findings in this cohort of patients treated with SRS. In contrast, Shakur et al demonstrated that pulsatility in the ipsilateral artery increased after only surgery and not embolization 30 . They postulated that redistribution of flow after embolization and maintenance of low pulsatility index may be associated with lower rates of rupture.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These include time-resolved imaging of contrast kinetics MRA, 17 4D radial acquisition contrast-enhanced MRA (4D rCE-MRA), 19 4D flow MRI using constrained reconstruction (HYPRflow), 16,17 MR-tractography, 29 functional MRI (fMRI), and quantitative MRA. 15,[24][25][26] Time-resolved imaging of contrast kinetics MRA, 4D rCE-MRA, and HYPRflow are particularly useful to characterize the anatomic features of bAVMs. As opposed to DSA, these imaging modalities are noninvasive and in the future may have the potential to provide similar information to DSA.…”
Section: Nonstandard Abbreviations and Acronymsmentioning
confidence: 99%
“…[12][13][14] Resistance of the vessels is sensitive to the change of flow dynamics according to the downstream structure and could be used to understand the angioarchitecture of shunting diseases. [14][15][16] Therefore, by precisely recording the pressure waveform from the tip of the microcatheter, it could be possible not only to measure the mean pressure but also to extract useful information by analyzing the waveform itself.…”
mentioning
confidence: 99%